2002
DOI: 10.1093/intqhc/14.5.393
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' perspectives on the quality of postpartum care in Central Shanghai, China

Abstract: Mothers indicated that to improve quality of services further, greater emphasis should be placed on: (1) health education on childcare; (2) more time allocation for discussion with health workers during their postpartum home visits so their questions and concerns could be addressed effectively; (3) access to health workers in times of need rather than during officially prescribed home visits; and (4) provision of continuous training for maternal and child health workers with respect to childcare. The findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 19 publications
3
22
1
2
Order By: Relevance
“…Participants indicated that postpartum services were not long enough and there was inadequate time for them to ask questions, indicating that the nurses' time with them and their babies was too short and insufficient. First-time teenage mothers in the Lomoro et al (2002) study indicated that nurses explaining everything to them prior to the baby coming being born, allowing time to sit and talk, and explaining everything thoroughly to her about her baby were behaviors most indicative of caring, and a similar finding was found in this study. Winfield et al (2000) found the human needs assistance scale (m = 4.70) was the highest ranked subscale while the existential/phenomenological/spiritual forces scale (m = 4.01) ranked as the least important scale.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Participants indicated that postpartum services were not long enough and there was inadequate time for them to ask questions, indicating that the nurses' time with them and their babies was too short and insufficient. First-time teenage mothers in the Lomoro et al (2002) study indicated that nurses explaining everything to them prior to the baby coming being born, allowing time to sit and talk, and explaining everything thoroughly to her about her baby were behaviors most indicative of caring, and a similar finding was found in this study. Winfield et al (2000) found the human needs assistance scale (m = 4.70) was the highest ranked subscale while the existential/phenomenological/spiritual forces scale (m = 4.01) ranked as the least important scale.…”
supporting
confidence: 84%
“…In Sauls's (2004) study on adolescent mothers' perceptions of nurse care during the childbirth experience, the top 10 labor support behaviors that were most helpful were as follows: (1) praised me; (2) gave me pain medication; (3) accepted what I said and did so without judgment; (4) appeared calm and confident when giving care; (5) made me feel cared about as an individual; (6) treated me with respect; (7) attempted to lessen demands on me; (8) answered my questions; (9) provided distractions by talking to me; (10) assisted me in breathing/relaxing. Lomoro et al (2002) reported that 50% of participants stated that the services received during postpartum were not of high quality. Participants indicated that postpartum services were not long enough and there was inadequate time for them to ask questions, indicating that the nurses' time with them and their babies was too short and insufficient.…”
mentioning
confidence: 99%
“…It is also supported by a recent report that there is about 65 to 75% potential for productivity increase by health workers in Tanzania if working time is spent on productive activities and the activities are done efficiently (Maestad, 2006). Moreover, availability of health professionals has a bearing on the quality of service that is offered and certainly on users' perception as reported from other studies (Smith & Sanderson, 1992;Haddad et al, 1998;Lomoro et al, 2002;Leon, 2003;Groenewegen et al, 2005;Lim et al, 2004;Manongi et al, 2006;Kamuzora & Gilson, 2007).…”
Section: Discussionmentioning
confidence: 86%
“…This result insisted the need for complete post -partum health advices for these women because exposure to work outside the home gives women better chances of contact with a more experienced persons and to acquire valuable health and social information. In addition, Three quarters of the women were living in rural areas while the rest were living in urban areas .This reflected women's needs for more health advices and extension of postpartum care services to the community where mothers are receiving care during home visits'' (4) . Women who had childbirth preparation and expectations for labor, met a higher level of education and employment, had higher global satisfaction with the childbirth experience (5) Part ІІ:-Discussion of the Woman's Reproductive Parameters:- Table (2) shows that the highest percentage of the sample is reported at primi gravid, and they are accounted (36.0%),and (57%) are ranged between primipara and second birth.…”
Section: Discussionmentioning
confidence: 99%
“…According to the use of breast feeding. Table ( 4) show that the majority of the study sample (86%) are use breast feeding and the causes related to that (83%) beliefs that mother milk gives immunity to the child,(80%) provide food for whole child,(78%) mother milk easy to digest, and (75%) breast feeding reduce disease of breast cancer also help in contraction after birth. According to use of artificial feeding the causes related to that (32%) of study sample think that mother milk not enough for child feeding, and (23%) of them think that the breast feeding restrict their activity.…”
Section: Methodsmentioning
confidence: 99%